Pengaruh Capital Intensity, Struktur Modal, Efektivitas Aset, dan Ukuran Perusahaan terhadap Nilai Perusahaan Subsektor Food and Beverage di Bursa Efek Indonesia - Meilanita Meilanita; Fransiska Enalia (MABIS, 2025)
This study aims to analyze the influence of capital intensity, capital structure, asset effectiveness, and firm size on the value of firms in the food and beverage subsector listed on the Indonesia Stock Exchange. The author employed associative quantitative research utilizing Eviews version 13. The population in this study consisted of 101 companies, and the sample size was 52 companies obtained through purposive sampling. Data analysis was conducted using descriptive statistical analysis, panel data models, classical assumptions (multicollinearity and heteroscedasticity), panel data regression analysis, the F-test, the coefficient of determination, and the t-test. The results of this study indicate that capital intensity has no effect on firm value, capital structure has a positive effect on firm value, asset effectiveness has no effect on firm value, and firm size has no effect on firm value. For further research, it is recommended to add other variables beyond assets, such as Return on Equity (ROE), profit growth, and corporate governance (GCG), as well as expand the research object and period.